Energy and Dynamics of Caveolae Trafficking - Matthaeus, Claudia; Taraska, Justin W. (Frontiers in Cell and Developmental Biology, 2021)
Caveolae are 70-100 nm diameter plasma membrane invaginations found in abundance in adipocytes, endothelial cells, myocytes, and fibroblasts. Their bulb-shaped membrane domain is characterized and formed by specific lipid binding proteins including Caveolins, Cavins, Pacsin2, and EHD2. Likewise, an enrichment of cholesterol and other lipids makes caveolae a distinct membrane environment that supports proteins involved in cell-type specific signaling pathways. Their ability to detach from the plasma membrane and move through the cytosol has been shown to be important for lipid trafficking and metabolism. Here, we review recent concepts in caveolae trafficking and dynamics. Second, we discuss how ATP and GTP-regulated proteins including dynamin and EHD2 control caveolae behavior. Throughout, we summarize the potential physiological and cell biological roles of caveolae internalization and trafficking and highlight open questions in the field and future directions for study